Antimicrobial effects of a pulsed electromagnetic field: an in vitro polymicrobial periodontal subgingival biofilm model. Issue 7 (8th August 2020) - Faveri, Marcelo; Miquelleto, Danilo Eduardo Calgaro; Bueno-Silva, Bruno; Pingueiro, João Marcos Spessoto; Figueiredo, Luciene Cristina; Dolkart, Oleg; Yakobson, Elad; Barak, Shlomo; Feres, Magda; Shibli, Jamil Awad
Abstract: The objective was to test the influence of a pulsed electromagnetic field (PEMF) on bacterial biofilm colonization around implants incorporated with healing abutments. Healing abutments with (test group) and without (control group) active PEMF devices were placed in a multispecies biofilm consisting of 31 different bacterial species. The biofilm composition and total bacterial counts (x10 5 ) were analyzed by checkerboard DNA-DNA hybridization. After 96 h, the mean level of 7 out of the 31 bacterial species differed significantly between groups, namely Eubacterium nodatum, Fusobacterium nucleatum ssp. nucleatum, Streptococcus intermedius, Streptococcus anginosus, Streptococcus mutans, Fusobacterium nucleatum ssp. Vicentii and Capnocytophaga ochracea were elevated in the control group ( p < 0.05). The mean total bacterial counts were lower in the Test group vs the control group ( p < 0.05). An electromagnetic healing cap had antimicrobial effects on the bacterial species and can be used to control bacterial colonization around dental implants. Further clinical studies should be conducted to confirm these findings.